Cyclic Triindoles and Tetraindoles: Substituent and Symmetry Effects on their Structural and Electronic Characteristics - Ruiz-Delgado, María del Carmen; Ruiz, Constanza; López-Navarrete, Juan Teodomiro; Gómez-Lor, Berta (My University, 2016)
During the last decade heptacyclic 10,15-dihydro-5H-diindolo[3,2-a:3',2'-c]carbazole (triindole) has been extensively studied as a new π-conjugated platform in the construction of self-assembling materials for optoelectronics. Specially remarkably is the record hole mobility values determined on triindole liquid crystals.1 In order to facilitate the design of new materials on a molecular basis and establish clear guidelines to fine tuning electronic parameters, we have recently synthesized new triindole and tetraindole-based systems.2-3 Our joint experimental and theoretical investigation shows that N-substitution, symmetry lowering of the platform, and insertion of π-spacers in extended dimers strongly impact on the fundamental electronic properties of triindoles.2 In addition, saddle-shaped tetraindoles are found to be an interesting 3D rigid scaffold to obtain electroactive molecules with increased dimensionality.3 We hope that this study can not only advance useful structure-property relationships of conjugated indole-based systems but also guide the design of new materials with potential applications in organic electronics.References 1. E.M. García-Frutos, U.K. Pandey, R. Termine, A. Omenat, J. Barberá, J.L. Serrano, A. Golemme, B. Gómez-Lor, Angew. Chem. Int. Ed. 2011, 50, 7399 2. a) C. Ruiz, J.T. López Navarrete, M.C.Ruiz Delgado, B. Gómez-Lor, Org. Lett. 2015, 17, 2258−2261. b) C. Ruiz, E.M. García-Frutos, D.A. da Silva Filho, J.T. López Navarrete, M.C. Ruiz Delgado, and B. Gómez-Lor, J. Phys. Chem. C 2014, 118, 5470−5477 3. C. Ruiz, A. Monge, E. Gutiérrez-Puebla, I. Alkorta, J. Elguero, J. T. López Navarrete, M.C. Ruiz Delgado and B. Gómez-Lor, submitted
Keywords: Semiconductores orgánicos; Conjugated materials; Organic semiconductors